COVID-19 policies and tuberculosis services in private health sectors of India, Indonesia, and Nigeria - Nathaly Aguilera Vasquez; Charity Oga-Omenka; Vijayashree Yellappa; Bony Wiem Lestari; Angelina Sassi; Surbhi Sheokand; Bolanle Olusola-Faleye; Lavanya Huria; Laura Jane Brubacher; Elaine Baruwa; Bachti Alisjahbana; Madhukar Pai (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Introduction: The COVID-19 pandemic created unprecedented challenges in the field of global health. Nigeria, Indonesia and India are three high tuberculosis (TB) burden countries with large private health sectors. Both TB and the private health sector faced challenges in these countries because of COVID-19. This study aimed to compare the COVID-19 control measures and policies in the provision of TB care services and gain insights from policymakers on how the pandemic affected the provision of TB services in the private healthcare sector, how each country adapted, and identify lessons learned for health system preparedness. Methods: Qualitative, in-depth interviews were conducted among a purposive sample of 11 national and sub-national policymakers in each country. Thematic content analysis was conducted on the data collected using an adapted WHO Health Equity Policy Framework. Results: Results revealed three policy dimensions under costs, access, and quality. Under healthcare costs, policymakers highlighted resource allocation and diversion of TB resources to COVID response, and increased operational costs for private provider. Under healthcare access, key themes included reduced TB case detection due to fear of COVID-19, disrupted diagnostic services, and adaptations such as extended medicine supplies and tele-consultations. Under healthcare quality, themes included compromised TB diagnostic accuracy due to similar respiratory symptoms with COVID-19, and strain on laboratory infrastructure due to competing demands from both diseases. Policymakers across the three countries pointed to the need for strengthening private–public partnerships (PPP) for healthcare service delivery and continued private sector investment to facilitate the continuity of TB care within a pandemic context. Conclusion: The results of this study provide an overview of the impact of the pandemic from the perspective of private facilities and policymakers in Nigeria, Indonesia and India, which can inform future policy and ways forward in strengthening PPP for healthcare service delivery in high TB burden countries.